2007
DOI: 10.1177/0013916506295574
|View full text |Cite
|
Sign up to set email alerts
|

Kitchenscapes, Tablescapes, Platescapes, and Foodscapes

Abstract: Built environments at many scales influence the type and amount of food consumed. Macroscale food systems and food landscapes influence food choices, and microscale rooms, furniture, containers, and objects influence food intake. The authors review literature about how four ubiquitous microscale built environments are persistent but often unrecognized influences on food intake. Kitchenscapes influence food intake through availability, diversity, and visibility of foods; tablescapes through variety, abundance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(75 citation statements)
references
References 77 publications
(80 reference statements)
2
59
0
4
Order By: Relevance
“…We point to the numerous research studies that show children and adults tend to eat more when given larger portion sizes (Fisher, Rolls, andBirch 2001, 2003;Kral, Roe, and Rolls 2004;Kral et al 2002;Sobal and Wansink 2007;Rolls, Engell, and Birch 2000;Nisbett 1968;Rolls, Morris and Roe 2002;Wansink 2004Wansink, Painter, and North 2005). For example, Levitsky and Youn (2004) report that young adults, served larger portions from one week to the next increase their consumption the next week by as much as 40%.…”
Section: Relevant Literaturementioning
confidence: 79%
“…We point to the numerous research studies that show children and adults tend to eat more when given larger portion sizes (Fisher, Rolls, andBirch 2001, 2003;Kral, Roe, and Rolls 2004;Kral et al 2002;Sobal and Wansink 2007;Rolls, Engell, and Birch 2000;Nisbett 1968;Rolls, Morris and Roe 2002;Wansink 2004Wansink, Painter, and North 2005). For example, Levitsky and Youn (2004) report that young adults, served larger portions from one week to the next increase their consumption the next week by as much as 40%.…”
Section: Relevant Literaturementioning
confidence: 79%
“…More successful habit change strategies likely target the specific contextual triggers of habitual behavior. These include vigilant monitoring of the unwanted response (Quinn, Pascoe, Wood & Neal, 2010), environmental re-engineering (e.g., Verplanken & Wood, 2006), and stimulus control techniques to reduce exposure to the triggers (Sobal & Wansink, 2007).…”
Section: Discontinuity Between Habit Mechanisms and Self-perceptionsmentioning
confidence: 99%
“…For example, interventions that alter subtle cues in eating situations have been shown to control eating habits. Sobal and Wansink (2007) demonstrated that the amounts of food and drink that people serve and consume decrease with smaller sizes of plates, spoons, and glasses. Smaller plates lead to lesser food intake, because people habitually consume around 92% of what they serve themselves (Wansink & van Ittersum, 2011), that is, habitual control of food intake is cued by the amount of food on a plate (Wansink & Cheney, 2005).…”
Section: Influencing Habitual Actionsmentioning
confidence: 99%